Chromosome doubling mediates superior drought tolerance in Lycium ruthenicum via abscisic acid signaling. (1st April 2020) - Rao, Shupei; Tian, Yuru; Xia, Xinli; Li, Yue; Chen, Jinhuan
Abstract: Plants are continuously affected by unfavorable external stimuli, which influences their productivity and growth. Differences in gene composition and expression patterns lead homologous polyploid plants to exhibit different physiological phenomena, among which enhanced environmental adaptability is a powerful phenotype conferred by polyploidization. The mechanisms underlying the differences in stress tolerance between diploids and autotetraploids at the molecular level remain unclear. In this research, a full-length transcription profile obtained via the single-molecule real-time (SMRT) sequencing of high-quality single RNA molecules for use as background was combined with next-generation transcriptome and proteome technologies to probe the variation in the molecular mechanisms of autotetraploids. Tetraploids exhibited an increase in ABA content of 78.4% under natural conditions and a superior stress-resistance phenotype under severe drought stress compared with diploids. The substantial differences in the transcriptome profiles observed between diploids and autotetraploids under normal growth conditions were mainly related to ABA biosynthesis and signal transduction pathways, and 9-cis-epoxycarotenoid dioxygenase 1 ( NCED1 ) and NCED2, which encode key synthetic enzymes, were significantly upregulated. The increased expression of the ABRE-binding factor 5-like ( ABF5-like ) gene was a pivotal factor in promoting the activation of the ABA signaling pathway and downstream target genes. In addition, ABA strongly induced the expression of osmotic proteins to increase the stress tolerance of the plants at the translational level. We consider the intrinsic mechanisms by which ABA affects drought resistance in tetraploids and diploids to understand the physiological and molecular mechanisms that enhance abiotic stress tolerance in polyploid plants.